Proceedings of 5th International Conference on Recent Advances in Space Technologies - RAST2011 2011
DOI: 10.1109/rast.2011.5966868
|View full text |Cite
|
Sign up to set email alerts
|

Plasma manipulation using a MHD-based device for a communication blackout in hypersonic flights

Abstract: When a vehicle flies with hypersonic velocity, a weakly ionized plasma layer is generated around the vehicle due to the shock heated air. Since the created plasma layer has a high electron number density, the vehicle has a communication difficulty known as radio blackout. In this study, we propose an innovative concept of a mitigation scheme based on MHD. The proposed mitigation scheme uses an ExB layer to manipulate the plasma density in a specific region during hypersonic flights. Due to the reduced electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Belov et al [5] investigated the effects of body shape on the mitigation effect via wind tunnel tests. Kim et al [6,7] reported a method to control the plasma density by applying a magnetic field around the vehicle, and the mitigation effect was experimentally demonstrated by Steffens et al [8]. Jung et al [9] and Takasawa et al [10] showed both numerically and experimentally that catalysis of the surface of the body head promotes recombination reactions in the plasma and reduces the ambient electron number density.…”
Section: Introductionmentioning
confidence: 99%
“…Belov et al [5] investigated the effects of body shape on the mitigation effect via wind tunnel tests. Kim et al [6,7] reported a method to control the plasma density by applying a magnetic field around the vehicle, and the mitigation effect was experimentally demonstrated by Steffens et al [8]. Jung et al [9] and Takasawa et al [10] showed both numerically and experimentally that catalysis of the surface of the body head promotes recombination reactions in the plasma and reduces the ambient electron number density.…”
Section: Introductionmentioning
confidence: 99%